Pengembangan Literasi Digital untuk Meningkatkan Kemampuan Membaca - Sri Fatikha Khoeriyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The rapid development of technology today should be the main key in efforts to develop students' abilities and skills in the field of education and the learning process in dealing with the world of technology and information. The support and role of education is expected to increase the nation's competitiveness in the midst of global competition. The openness of information technology should be balanced with the progress of good reading literacy, but in Indonesia in particular, reading literacy skills for children are still at the bottom. Therefore, the development of digital literacy is expected to be a benchmark and a supporting factor in the development of student knowledge that can be accessed by digital media around the environment such as mobile phones, computers, laptops, etc. This article proposes a new conceptual framework for the concept of digital literacy, combining five types of literacy: (a) photovisual literacy; (b) reproductive literacy; (c) information literacy; (d) branched literacy; and (e) socio-emotional literacy that can support knowledge development.